2017
DOI: 10.1016/j.envpol.2017.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, fate and transformation of emerging contaminants in water: An overarching review of the field

Abstract: Many of the products and drugs used commonly contain chemical components which may persist through sewage treatment works (STW) and eventually enter the aquatic environment as parent compounds, metabolites, or transformation products. Pharmaceuticals and personal care products (PPCPs) and other emerging contaminants (ECs) have been detected in waters (typically ng/L) as well as more recently bound to sediment and plastic particles (typically ng/g). Despite significant advancement of knowledge since the late 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
170
0
19

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 572 publications
(218 citation statements)
references
References 151 publications
2
170
0
19
Order By: Relevance
“…Summary of significant regulation set on the sale, manufacture and import of products containing plastic microparticles across the world until July 2018, see also: Hurley et al[174] Wilkinson et al[186].…”
mentioning
confidence: 99%
“…Summary of significant regulation set on the sale, manufacture and import of products containing plastic microparticles across the world until July 2018, see also: Hurley et al[174] Wilkinson et al[186].…”
mentioning
confidence: 99%
“…EPs are a wide range of substances of emerging concern, priority and persistence, and they generate severe hazards to the environment or toxicity to the human, but many of them lack proper monitoring methods and the process of being regulated is not yet fully understood (Ncibi et al 2017) (Wilkinson et al 2017).…”
Section: Overview Of Epsmentioning
confidence: 99%
“…Hence, many studies paid close attention to the contaminations in rivers and lakes. Wilkinson et al (2017) reviewed the occurrence, fate and transformation of EPs in water, and reported that many types of Eps including pharmaceuticals and PPCPs have been detected in waters with the typically concentration of the ng/L. In Laurentian Great Lakes, a total of 32 chemicals were detected in water samples and their concentrations including flame retardants, alkylphenols and sterols, were ubiquitous across 27 field sites in six Great Lakes watersheds and the total concentration was as high as (Thomas et al 2017 According to the literature reports, several types of PPCPs found in 25 different nations were summarized in detail (Kwon and Lee 2017), and a variety of emerging chemicals of concern from PPCPs, It's worth noting that the concentration of ciprofloxacin, SMX, amoxicillin, norfloxacin, and ofloxacin in Indian wastewater treatment plant were up to 40 times higher than that in other countries in Europe, Australia, Asia and North America.…”
Section: Occurrence Of Eps In Water Environmentsmentioning
confidence: 99%
“…Results obtained by animal models, human clinical test and epidemiological studies have shown that EDCs have a strong association with several health effects [6]. The EDCs are a broad class of molecules, including pharmaceutical, organochlorinated compounds; components of personal care products with different sources and widespread uses and applications within industrial processes, and farming and agricultural activities; and household items [7]. Accordingly, their occurrence in the environment could be a potential risk for the human health, the survival of populations, the sustainability of the ecosystems and the economy of the countries [8].…”
Section: Introductionmentioning
confidence: 99%